2013
DOI: 10.1175/jcli-d-13-00134.1
|View full text |Cite
|
Sign up to set email alerts
|

ENSO-Modulated Cyclogenesis over the Bay of Bengal*

Abstract: The role of the El Niño–Southern Oscillation (ENSO) on the modulation of tropical cyclone activity over the Bay of Bengal (BoB) for the 1979–2011 period is examined. It is shown that Niño-3.4 sea surface temperature (SST) anomalies are negatively correlated with the BoB tropical cyclone activity to a statistically significant percentage by a lead time of 5 months. Composites of 10-m zonal winds exhibit greater variance during La Niña events, favoring the development of low-level cyclonic vorticity. Low vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
1
54
0
Order By: Relevance
“…TC incidence in various formation basins is strongly tied to ENSO variations . Thus, any substantial change in the behavior of ENSO in a warmer world would cause substantial accompanying changes in TC formation regions and tracks.…”
Section: Observations Of Tcsmentioning
confidence: 99%
“…TC incidence in various formation basins is strongly tied to ENSO variations . Thus, any substantial change in the behavior of ENSO in a warmer world would cause substantial accompanying changes in TC formation regions and tracks.…”
Section: Observations Of Tcsmentioning
confidence: 99%
“…Research relating to the physical characteristics of tropical cyclones focuses on their genesis (Sadhuram et al , ; Kotal et al , ; Yokoi and Takayabu, ); relationships with SSTs and the El Niño Southern Oscillation (ENSO) (Singh et al , ; Mandke and Bhide, ; Kotal et al , ; Kikuchi and Wang, ; Girishkumar and Ravichandran, ); the curvature of tropical cyclone tracks (Murty and Neralla, ); their climatology including frequency, seasonality and interannual variability (Khan et al , ; Singh, ; Li et al , ), landfall locations (Azam et al , ) and the height of storm surges (As‐Salek, ; Azam et al , ; Dube et al , , ; Jakobsen et al , ). The ENSO is the dominant mode of interannual climate variability globally (McPhaden, ) and this influences tropical cyclone activity (frequency, genesis location and intensity) in the Bay of Bengal (Singh et al , ; Camargo et al , ; Girishkumar and Ravichandran, ; Felton et al , ). By undertaking numerical simulations, As‐Salek () suggested that those tropical cyclones that made landfall along the Noakhali–Chittagong coast triggered greater storm surge heights than those that made landfall along the Chittagong–Cox's Bazar coast (Figure ).…”
Section: Previous Studiesmentioning
confidence: 99%
“…More specifically, Felton et al . () found that the Niño‐3.4 index is negatively (and significantly) correlated with the BoB TC activity with a lead time of 5 months. It was also found in Girishkumar and Ravichandran () that during La Niña events the low‐level vorticity and TC heat potential are larger over the BoB than during El Niño and thus more favourable for TC development.…”
Section: Introductionmentioning
confidence: 99%